ANALISIS KONSEP DIRI SISWA SERTA IMPLIKASINYA DALAM PELAYANAN KONSELING - M. Putra Dinata Saragi (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
This research is motivated by the many problems students have in terms of self-concept. This study aims to describe students' self-concept. This research uses descriptive quantitative method. The population of the study population was Class XI and XII Students of Padang 8 Public High School, totaling 464 people. The sample amounted to 215 people, who were selected by the proportional stratified random sampling technique. The instrument used is scale. The results of the validity and reliability test of the self-concept instrument state that the research instrument is valid and reliable. Data were analyzed by descriptive statistics. The findings of this study show that on average students' self-concept images are in the positive category. The implications of the results of the study can be used as input to make a program of guidance and counseling services.Keywords: Self Concept, Implication of Guidance and Counseling